1994
DOI: 10.1051/jp4:1994628
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in low temperature infrared detectors

Abstract: this paper indicates the state of progress of advanced infrared detection arrays in the world. This presentation is focused on high-performance cooled detectors i.e. CdHgTe photovoltaic arrays (which are more particularly emphasized), InSb detectors, PtSi Schottky barrier diode arrays, extrinsic silicon photoconductors and 111-V multi-quantum well detectors. It is shown that interest may be focused on parameters other than the intrinsic detector performance alone. Future trends concerning the technologies are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Similarly low values were obtained by Lebedev (85) at 150 GHz using microwave technology. We found that in homodyne operation, hot electron bolometers perform significantly better as detectors than Schottky diode detectors (94,95), especially when the background power can be suppressed, as in the shunt resonator discussed below, but their responses are too slow for pulse experiments.…”
Section: Quasi-optical Transmission Spectrometermentioning
confidence: 83%
“…Similarly low values were obtained by Lebedev (85) at 150 GHz using microwave technology. We found that in homodyne operation, hot electron bolometers perform significantly better as detectors than Schottky diode detectors (94,95), especially when the background power can be suppressed, as in the shunt resonator discussed below, but their responses are too slow for pulse experiments.…”
Section: Quasi-optical Transmission Spectrometermentioning
confidence: 83%
“…A general molecular synthetic route to access ternary nanoclusters is desirable since ternary materials find widespread applications in optical and electronic devices. For example Hg 1-x Cd x Te (x ) 0-1) has been used in IR detection 7 and CuInS 2 (E g ) 1.5 eV) semiconducting thin films display desirable properties for use in solar cells applications. 8 We communicated recently 9 that tris(tripropylphosphine)copper (trimethylsilyl thiolate), (Pr 3 P) 3 Cu-SSiMe 3 , may be used as a soluble source of "copper thiolate", "CuS -", in the formation of a mercury-copper-sulfide cluster.…”
Section: Introductionmentioning
confidence: 99%
“…A general molecular synthetic route to access ternary nanoclusters is desirable since ternary materials find widespread applications in optical and electronic devices. For example Hg 1 - x Cd x Te ( x = 0−1) has been used in IR detection and CuInS 2 ( E g = 1.5 eV) semiconducting thin films display desirable properties for use in solar cells applications …”
Section: Introductionmentioning
confidence: 99%